Formulation and evaluation of buccoadhesive quetiapine fumarate tablets - Appa Rao Potu; Naresh Pujari; Shashidher Burra; Prabhakar Reddy Veerareddy (Universidade de São Paulo, 2012)
The aim of present study was to develop and evaluate buccoadhesive Quetiapine Fumarate (QF) tablets, which is extensively metabolised by liver. Buccoadhesive tablets of QF were prepared using HPMC K4M, HPMC K15M and combination of carbopol and HPC as mucoadhesive polymers by direct compression method. Sodium deoxycholate was added to formulation to improve the permeation of drug. The formulations were tested for bioadhesion strength, ex vivo residence time, swelling time and in vitro dissolution studies and ex vivo permeation studies. Optimized formulation (F3) showed 92% in vitro release in 8 h and 67% permeation of drug through porcine buccal mucosa and followed fickian release mechanism with zero order kinetics. FTIR studies of optimized formulation showed no evidence of interaction between the drug and polymers. In vivo mucoadhesive behaviour of optimized formulation was performed and subjective parameters were evaluated. O objetivo do presente estudo foi desenvolver e avaliar os comprimidos bucoadesivos de fumarato de quetiapina (FQ), que é extensivamente metabolizada no fígado. Os comprimidos bucoadesivos de FQ foram preparados utilizando-se HPMC K4M, HPMC K15M e a combinação de carbopol e HPC como polímeros mucoadesivos pelo método de compressão direta. O desoxicolato de sódio foi adicionado à formulação para melhorar a permeação do fármaco. As formulações foram testadas quanto à força de bioadesão, tempo de residência ex vivo, tempo de inchamento, dissolução in vitro e permeação ex vivo. A formulação otimizada (F3) mostrou 92% de liberação in vivo em 8 h e 67% de permeação do fármaco através da mucosa bucal de porco e seguiu o mecanismo fickiano de liberação com cinética de ordem zero. Os estudos de FTIR da formulação otimizada não mostraram evidência da interaço entre o fármaco e os polímeros. O comportamento mucoadesivo in vivo da formulação otimizada foi efetuado e avaliaram-se os parâmetros subjetivos.